Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Mediasi ( Studi Pada Karyawan Perkemahan Dusun Sahabat Alam ) - Nevio Prayoga Jon Hayon; Budi Wahono; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This research seeks to investigate and explain the impact of motivation and discipline concerning employee performance through job satisfaction as a mediator (a study of employees at the Perkemahan Dusun Sahabat Alam). A sample size of 40 respondents was collected. The analysis tools used were Multiple Linear Regression and PROCESS using SPSS. The results indicate that motivation has a positive and significant influence on employee job satisfaction at the Sahabat Alam Hamlet Campsite, but does not have a significant direct impact on employee performance. Meanwhile, work discipline has been shown to have a positive and significant influence on both job satisfaction and employee performance. Job satisfaction has also been shown to have a positive and significant influence on improving employee performance. Based on the results of the mediation analysis, job satisfaction is found to fully mediate the relationship between motivation and employee performance. On the other hand, in the relationship between work discipline and employee performance, job satisfaction acts as a partial mediator. Keywords: Motivation, Work Discipline, Employee Performance, Job Satisfaction